Perubahan Regulasi tentang Penanaman Modal di Bidang Industri Minuman Beralkohol Perspektif Sadd al-Dzariah - Sabila, Farahda Meitsa; Junaidi, Mohamad Hakim; Albana, Muhammad Abdur Rosyid (Al-Qisthu, 2024)
The government initially attempted to liberalize the alcoholic beverage industry by opening investment opportunities; however, public opposition prompted regulatory changes that ultimately closed investment in this sector. This study focuses on analyzing investment regulations in the alcoholic beverage industry from the perspective of sadd al-dzariah, aiming to evaluate the extent to which these regulations prevent harm. Employing a normative legal research method through document analysis, this study examines the regulatory shift from Presidential Regulation No. 10 of 2021 to Presidential Regulation No. 49 of 2021. The findings reveal that the liberalization of investment in this sector posed significant risks of moral and social degradation, while the regulatory amendments closing investment opportunities reflect preventive measures aligned with the sadd al-dzariah principle. This corrective action by the government underscores the relevance of Islamic legal principles in maintaining a balance between economic interests and public welfare in investment regulation policies.